1986
DOI: 10.1103/physrevlett.57.1207
|View full text |Cite
|
Sign up to set email alerts
|

Have QuasinuclearNN¯Bound States Been Discovered?

Abstract: It is suggested that a broad structure ^°(1480) recently observed in the reaction pn -* TT~X° -> 3TT~2TT + may be interpretable in terms of an unstable quasinuclear bound state of the (complex) nucleon-antinucleon (NN) potential. The observed mass, production branching ratio, and preference for the X°-* p°p° rather than TT + TT' decay mode are consistent with a quantum-number assignment /* c (/ c )»2 + + (0 + ). Prospects for finding the lower-lying 0 + + (0 + ) and 1'"(()-) members of the expected natural-par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Given that mass and width of the tensor agree with f 2 (1565), but disagree with f 2 (1640), it seems more natural to assign the 2 ++ signal to the former. It is interesting to note that a 2 ++ ρρ molecule (Törnqvist, 1991) or a 2 ++ baryonium state (Dover, 1986) decaying strongly to ρρ (Dover, 1991) are predicted in this mass range. The f 2 (1565) could be one of these states.…”
Section: F 2 (1565)mentioning
confidence: 95%
“…Given that mass and width of the tensor agree with f 2 (1565), but disagree with f 2 (1640), it seems more natural to assign the 2 ++ signal to the former. It is interesting to note that a 2 ++ ρρ molecule (Törnqvist, 1991) or a 2 ++ baryonium state (Dover, 1986) decaying strongly to ρρ (Dover, 1991) are predicted in this mass range. The f 2 (1565) could be one of these states.…”
Section: F 2 (1565)mentioning
confidence: 95%
“…It has no place in a q q scheme mainly because all nearby q q states are already occupied. Dover [39] has suggested that it is a "quasinuclear" N N bound state, and Törnqvist [31] that it is a deuteron-like (ωω+ρρ)/ √ 2 "deuson" state.…”
Section: Tensor Meson Nonetmentioning
confidence: 99%
“…It has no place in a q q scheme mainly because all nearby q q states are already occupied. Dover [28] has suggested that it is a "quasinuclear" N N bound state, and Törnqvist [17] that it is a deuteron-like (ωω + ρρ)/ √ 2 "deuson" state.…”
Section: Tensor Meson Nonetmentioning
confidence: 99%